Penerapan model pembelajaran CIRC (cooperative integrated reading and composition) berbantuan komik kuark untuk meningkatkan keterampilan membaca pemahaman - Wahyuningsih, Septiana; Istiyati, Siti (Didaktika Dwija Indria, 2026)
This research aims to improve the reading comprehension skills of fourth-grade students at SD Negeri Gebang 224 through the application of the Cooperative Integrated Reading and Composition (CIRC) learning model assisted by Kuark comics. Two cycles of Classroom Action Research (CAR) were used to conduct this study.  Planning, carrying out, observing, and reflecting make up each cycle.  Students and instructors in grade IV at Gebang 224 State Elementary School served as the study's subjects.  The fourth-grade students at SD Negeri Gebang 224 and papers (teaching modules, syllabus, and pictures taken during reading comprehension classes) serve as the research's data sources. There are both qualitative and quantitative data used.  Data gathering methods include documentation, testing, and observation.  Triangulation of methods and sources promotes data validity.  Collecting, reducing, presenting, and drawing conclusions are all parts of data analysis.  Reading comprehension abilities have significantly improved, according to the data.  Before the action, the average reading skill score was 62. In cycle I, it rose to 63.20, and in cycle II, it reached 78.79.  Additionally, the classical completeness increased in cycle I and II, rising from 20.83% in the pre-action stage to 41.67% and 83.33%, respectively.  The results of the study show that fourth-grade students at SD Negeri Gebang 224 Surakarta can improve their reading comprehension skills by utilizing Kuark comics in conjunction with the CIRC learning paradigm.